Thermal Treatments and Compensation Techniques for the Improved Response of FBG Sensors in POFs - Leal-Junior, Arnaldo Gomes; Theodosiou, Antreas; Marques, Carlos Alberto F.; José Pontes, Maria; Kalli, Kyriacos; Frizera, Anselmo (My University, 2018)
The influence of annealing under different humidity conditions on temperature, strain and transverse force performance of polymer optical fiber Bragg gratings (POFBG) inscribed in cyclic transparent amorphous fluoropolymers (CYTOPs) is presented. The POFBG are imprinted using direct-write, plane-by-plane femtosecond laser inscription method. Further improvement to the sensor's performance, with respect to sensitivity, linearity, and hysteresis, is obtained with a simple technique based on polymer viscoelastic response applied to the annealed POFBGs. The sensors were characterized for temperature, strain and transverse force after annealing and results show that sensors annealed under water have the lowest hysteresis. Additionally, the temperature sensitivity increased when the sensor was annealed in low humidity conditions. Finally, for strain and transverse force, the highest sensitivity was obtained in POFBG sensors annealed under water. The compensation technique did not show a substantial decrease in hysteresis response for applied strain tests; however, for temperature and transverse force tests, the hysteresis decreased by more than 2 and 4 times, respectively.
Keywords: Annealing; Fiber Bragg gratings; Hysteresis; Polymer optical fiber